Cost effeciency, capital and risk-taking in Asean banking - Abdul Mongid
Banks are regarded as the most important components of the financial system and their roles are essential to the performance of the economy. Bank for International Settlement (BIS) has found that, the operating costs of banks in many Asiane economies were not only high but inclined to rise in recent years. Because of this, banks must be efficient. The objectives of this thesis are: (i) to estimate the cost efficiency scores of banks in six countries in the Association of the Southeast Asian Nations (ASEAN) that is, Indonesia, Malaysia, Singapore, Thailand, and the Philippines and Vietnam; (ii) to investigate the determinants of banks' cost efficiency; and (iii) to investigate the importance of bank cost efficiency on capital position and risk taking. This study applies the Stochastic Frontier Analysis (SFA) to estimate bank cost efficiency of banking firms in ASEAN during 2003 to 2008. The panel data covers 633 observations. The data is gathered from the annual report of individual bank obtained from the Bankscope database. For the determinants of banks' cost efficiency. Tobit regression analysis is employed with cost efficiency score as the dependent variable. Bank specific variables (size, equity to total asset, loan to total asset, loan to deposit ratio, return on asset , risk, personnel expenses to total expenses , fixed asset to total asset, fixed asset to total asset, cost to income ratio and off-balance sheet activities to total asset) and environmental variables (economics growth, corruption index and index of economic freedom) are used as independent variables. For investigation on the importance of the banks' cost efficiency on capital position and risk taking, the study employed a three-stage regression method. Banks' cost efficiency, capital position and risk-taking are set as instrumental variables. The result for the banks' mean cost efficiency is 87.4%. In term of banks' cost efficiency according to country, the results show that Singapore is the most cost efficient banking market (89.1%), Thailand (87.7%), Vietnam (87.4%), the Philippines (86.6%) and Malaysia (85.9%). Using Tobit regression, the study finds that banks' cost efficiency is positively related to size, loan to total asset, personnel expenses to total expenses, off-balance sheet activities to total asset. This suggest that large -sized banking firms enjoy economies of scale as well as economies of scope in their production. Banks with more loans in their balance sheet, spend more on personnel and actively involved on innovative activities, have higher cost efficiency. In contrast, banks' cost efficiency is negatively related to ratio on fixed asset to total asset and cost to income ratio. For the environmental variables, this study finds that economic growth. corruption index and index of economic freedom, are positively related to banks' cost efficiency. The economic growth improved cost efficiency because in good economic condition, the expenses are relatively lower. On corruption, it is beyond the expectation, as higher corruption increase efficiency indicating the capabilities of banks to exploit the corrupt environment to improve their own cost efficiency. The economic freedom is positive as it implies that competition is important for the cost efficiency. On the interrelationship between bank cost efficiency, capital and risk taking, the study finds the following: (i) In the efficiency equation, size and equity to total asset are positive and significant. On the other hand, index of economic freedom is negativea and significant. The dummy for country are all positive and significant indicating cost efficiency as a country specific issue; (ii) In the capital equation, three bank specific variables (cost efficiency, cost to income ratio, return on asset), are positive and significant while two bank specific variables (loan to total asset and size) are negative and significant. Further, the results show that, index of economic freedom is positive and significant while the corruption index is negative and signficant. All dummy for country are negative and significant; (iii) In the risk taking equation, the study finds that risk taking is positively determined by banks' cost efficiency, return on asset, personnel expenses to total expenses and economic freedom. On the other hand, risk-taking is negatively determined by equity to total asset, loan loss provision to total loan, size, deposit to total asset, off-balance sheet activities to total asset and corruption index. In short, we can conclude that bank cost efficiency determines the capital position and risk-taking while banks' capital position and risk taking determine bank costefficiency. It means that, bank cost efficiency is the foundation for banks' capital position and risk-taking. These results suggest that, inorder to enhance ASEAN banking efficiency, the regulator needs to encourage merger, remunerate employess better, innovate, and invest more capital. The findings underline the importance of efficiency measure in banking management and supervision. Theoretically, the findings reject the A gency Theory in ASEAN banking.